دراسة تحليلية حول حصاة المسالك البولية وعلاقتها بالتاريخ المرضي السابق للعائلة - السوداني, ميثم عبد اليادي (University of Thi-Qar Journal of Science, 2013)
For the period form 1st of July 2012 to 1st of November 2012, fifty patients with urinary stone disease were questioned, from the patients whom consult for Urology out patients clinic in Al- Yarmouk teaching hospital, in Baghdad province-Iraq. 46 (92%) patients had relative had history of urinary stone disease ; and only 4(8%) patients had no family history .Another fifty patient had no history of urinary stone disease ,sampled randomly as control group ;results were found that 9 (18%) from control group had family history of urinary stone disease and 41(82%) had no history of such disease in their relatives Age groups of patients were assembled taking in consideration the gender of thepatient and their age group above 51 years old represent 29 patients and this equal to ( 63%). While patients with age group between 20 to 30 patients are only 4 and their representative percent was (8.69%).also, there was only 4 patients diseased with urinary stone disease and had no family history, also 46 patients diseased with urolithiasis and had positive family history of urolithiasis 41patients had no history of urolithiasis and had no family history of urinary stone disease .and 9 patients undiseased with urolithiasis and diseased relatives with urinary stone disease